Courts of Appeals in the Federal Judicial System - J. Woodford Howard Jr (Princeton University Press, 2014)
The object of this study is to help improve understanding of intermediate federal courts by analyzing the business and functions of three major tribunals in the flow of federal litigation and the attitudes of the judges toward their job and its chief problems. The unifying threads of the inquiry are two classic questions in American federalism and jurisprudence, both bearing on problems of institutional cohesion. First, what provides the glue binding federal courts into a judicial system? Second, what controls the personal discretion of circuit judges to make law and policy in the course of adjudication? To explore these questions we shall view the three tribunals from twin perspectives. The focus of Part I, formal and telescopic, is on intercourt relations. After setting the stage in Chapter One for readers unfamiliar with the organization of federal courts and their political setting, we shall analyze the business of the three circuits and their decisions in the stream of federal litigation (Chapters Two and Three). Of particular concern are their functions in the federal judicial system and their relations with other courts. How uniform or unique is the work of the circuit courts? How strong are formal controls—appellate review and reversal—in supervising lower courts at both appellate levels?